La planificación microcurricular que se ejecuta en el proceso de enseñanza -aprendizaje de las ciencias naturales y el desarrollo de destrezas con criterios de desempeño en los estudiantes del décimo año de educación general básica de la unidad educativa anexa a la Universidad Nacional de Loja, periodo 2012 – 2013 - Rivera Quilligana, Nancy Gabriela (2013)
In our country, the curriculum has been undergoing in a series of changes that seek to improve the quality of education. In this way, in 2010 the Curricular Updating and Strengthening of General Basic Education is proposed, which main purpose is to get the skills development with performance criteria in students; despite this, it is still evident that micro curricular planning, and teaching activity in general, do not focus on skills development with performance approach as the Ministry of Education propose. Confront this problem; it is proposed to carry out a research work titled "The micro curricular planning that runs in the Natural Science teaching – learning process and skills development with performance criteria in the students of tenth year of General Basic Education at Educational Unit Attached to the National University of Loja, academic period 2012 - 2013 ". The objective of this research work was: to analyze the influence of micro curricular planning in the skills development with performance criteria in the students of tenth year of General Basic Education at Educational Unit Attached to the National University of Loja, and to propose viable alternatives that contribute to invent the micro curricular planning to promote skills development with performance approach. It worked with a representative sample of the population composed of teachers and students of the school community; also a sample of micro curricular planning was analyzed. Moreover, as research techniques a survey to teachers and students was applied and the hermeneutic study of micro curricular planning. The micro curricular planning that Natural Science’s teachers carry out, influences in the skills development with performance criteria in the students of tenth year of General Basic Education at Educational Unit Attached to the National University of Loja. The obtained results allowed to conclude that in the micro curricular planning that teacher carry out and execute, the proposed guidelines in the Curricular Updating and Strengthening of General Basic Education are not considered; why, the skills with performance criteria which are developed in students primarily attend to the knowledge acquisition, so that a prevalence of cognitive environment and little development of deepening accuracies is evident.